Penggunaan Pembelajaran Kontekstual dengan Pembelajaran Konvensional - Indriyani, Desi; Silvinia, Silvinia; Lubis, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This reseach aims at finding out a significant difference of students cognitive learning outcomes of Natural Science subject between the Contextual and Conventional Learning. This quasi experiment applied the two group post-test only design. The samples were students of class VA and VB of SDN 09 Belakang Balok, Bukittinggi. 30 students of class VA acted as the experimental class, which was taught using the contextual learning. Meanwhile, 30 students of class VB acted as the control class that was taught using the conventional learning. They were selected using the simple random sampling technique. Based on the t-test of the students post-test scores, it was found that tcount 4,74> ttable 1,67155 α 0,05. It means the contextual learning isi better compared to the conventional one.Keywords: the contextual learning, the conventional learning, students cognitive learning outcomes of natural science subject.